Hubungan Pengawasan Orang Tua dan Riwayat Keluarga dengan Perilaku Merokok pada Remaja di Desa Lemah Putih - Hanif Alya Nugraheni; Nustrisia Nu’im Haiya (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Adolescence is a period marked by a tendency to imitate behaviors associated with adulthood, including risky behaviors such as smoking. Smoking is a common habit among adolescents and can have negative long-term effects on health. This study aims to examine the relationship between parental supervision and family history with smoking habits in adolescents in Lemah Putih Village. The study used a quantitative approach with a cross-sectional design and involved 144 adolescents selected through purposive sampling. The instruments used were questionnaires on adolescent smoking behavior, the level of parental supervision, and family history of smoking. The results showed that the majority of respondents were in the late adolescent age group (17-20 years) at 51.4%, mostly male (87.5%), and had a high school education level (53.5%). About 50.7% of respondents had a high level of parental supervision, while 61.8% had a family history of smoking. Moderate smoking behavior was found in 45.1% of respondents. Data analysis revealed a significant relationship between parental supervision and adolescent smoking behavior, as well as a connection between family history of smoking and smoking habits in adolescents in Lemah Putih Village. Therefore, strict parental supervision and awareness of family history play an important role in reducing smoking behavior in adolescents. It is expected that the findings of this study will provide insights for parents and relevant parties to pay more attention to supervising their children and reduce smoking habits among adolescents.